The Problem Of The Neutrality Of The Civil Service In Local Head Elections: A Constitutional Law Perspective - Christina Bagenda; Mohammad Solekhan; Muchamad Taufiq; Ernesta Arita Ari; Jusuf Luturmas (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The neutrality of the State Civil Apparatus in local democratic contests, particularly Regional Head Elections, constitutes a fundamental principle for the realization of a clean, professional, and democratic system of governance. As an integral component of the state apparatus, ASN plays a strategic role in public administration and service delivery, thereby requiring impartiality and freedom from practical political interests. Nevertheless, empirical realities indicate that violations of ASN neutrality during Pilkada remain prevalent, manifesting in both direct and indirect political involvement, misuse of state resources, and administrative actions that favor certain candidate pairs. This condition reflects a persistent gap between normative legal frameworks and their practical implementation. This article aims to examine the challenges surrounding ASN neutrality in Pilkada by analyzing regulatory arrangements, implementation practices, and supervisory mechanisms from a constitutional law perspective. Employing a normative juridical approach, this study reviews statutory regulations, legal doctrines, and findings from relevant national scholarly journals. The analysis reveals that although the legal framework governing ASN neutrality is relatively comprehensive, the effectiveness of law enforcement and oversight mechanisms continues to face significant obstacles. These include weak inter-institutional coordination among supervisory bodies, political pressures exerted on the bureaucracy, and a limited level of legal awareness among certain segments of ASN. From the standpoint of constitutional law, breaches of ASN neutrality have serious implications for the quality of democracy, the realization of good governance principles, and the legitimacy of local governments produced through Pilkada. Therefore, strengthening legal policies, enhancing supervisory capacity, and reinforcing bureaucratic ethics development are essential measures to ensure the consistent enforcement of ASN neutrality in every local democratic process.